(untitled) (REMUNOM, 2024)
The growing demand for high quality vegetables, with sustainable origin and cultivation, has become an influential factor in the producer market. The present work has the general objective of evaluating the efficiency of using alternative organic substrates in the germination performance and initial growth of cherry tomato seedlings grown in pots. The experiment was conducted in a greenhouse, at the Chapadinha Science Center at the Federal University of Maranhão. A completely randomized design was adopted, with four treatments and thirty replications, constituting 4 experimental units, one plant per pot after thinning. The treatments consisted of: T1: 60% soil + 40% decomposed babassu stem (CDB); T2: 60% soil + 40% commercial substrate (SC); T3: 60% soil + 40% cattle manure (EB); T4: 60% soil + 40% washed sand (AL). Sowing was carried out in expanded polystyrene trays, with 128 cells and transplantation was carried out when the seedlings had five definitive leaves, in pots. The following were evaluated: emergence speed index (IVE), germination percentage (PG), plant height (ALT) and number of leaves (NF). Treatments using decomposed babassu stem and cattle manure showed better results for emergence speed index, germination percentage, seedling height and number of leaves, with results similar to the use of commercial substrate. Both the decomposed babassu stem (CDB) and the coil manure (EB) provided nutritional additions for the production of cherry tomato seedlings grown in pots, in addition to influencing the improvement of the physical characteristics of the substrate, aiding in better germination and increased development initial biometric of the seedlings, corroborating a result similar to the commercial substrate, and can largely replace it.